1991
DOI: 10.1111/j.1600-0404.1991.tb05003.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of central and peripheral motor conduction in normal subjects

Abstract: Motor potentials to transcranial and cervical magnetic stimulation and F-wave were recorded in 37 arms of 25 normal subjects. Clockwise and anticlockwise cervical stimulation were performed over C5, C7 and T2 spinous processes. A significant correlation was found between height and measurements of central and peripheral motor conduction. Peripheral motor conduction measured by F-wave derived techniques (Kimura formula) was 0.5 msec higher as compared with responses to cervical magnetic stimulation. The site an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…There is a wide range of MT values in healthy subjects; the present authors observed MTs ranging from 26 to 60% for lower MT, 34 to 67% for upper MT, and 29 to 68% for movement MT, which corroborate the range of MT values previously reported (Mills & Nithi, 1997;Conforto et al, 2004). MEP latencies ranged from 20.07 ± 2.05 ms (for the ulnar MEP latency on the right) to 20.77 ± 1.39 ms (for the median MEP latency on the right), which are in agreement with MEP latencies reported by several authors (Barker et al, 1987;Chu, 1989;Ghezzi et al, 1991;Ravnborg & Dahl, 1991;Furby et al, 1992;Mills & Nithi, 1997). Motor evoked latencies demonstrated consistency across the six test sessions, with ICCs of 0.87 and 0.92 for the median MEP latencies (on the right and left upper extremities, respectively); ulnar MEP latency ICCs were 0.87 (right) and 0.85 (left).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…There is a wide range of MT values in healthy subjects; the present authors observed MTs ranging from 26 to 60% for lower MT, 34 to 67% for upper MT, and 29 to 68% for movement MT, which corroborate the range of MT values previously reported (Mills & Nithi, 1997;Conforto et al, 2004). MEP latencies ranged from 20.07 ± 2.05 ms (for the ulnar MEP latency on the right) to 20.77 ± 1.39 ms (for the median MEP latency on the right), which are in agreement with MEP latencies reported by several authors (Barker et al, 1987;Chu, 1989;Ghezzi et al, 1991;Ravnborg & Dahl, 1991;Furby et al, 1992;Mills & Nithi, 1997). Motor evoked latencies demonstrated consistency across the six test sessions, with ICCs of 0.87 and 0.92 for the median MEP latencies (on the right and left upper extremities, respectively); ulnar MEP latency ICCs were 0.87 (right) and 0.85 (left).…”
Section: Resultssupporting
confidence: 92%
“…In clinical diagnosis and laboratory research, the possible effects of subject's gender, body height and upper limb length, and handedness on neurophysiological measures are important considerations (Ghezzi et al, 1991). Gender (van der Kamp et al, 1996;Mills & Nithi, 1997), height (Ghezzi et al, 1991;Toleikis et al, 1991;Wochnik-Dyjas et al, 1997), upper limb length (Ghezzi et al, 1991), and hand dominance (Macdonell et al, 1991) may contribute to variability of MEP responses, although conflicting results have been reported in the literature (Chu, 1989;Claus, 1990;Eisen & Shytbel, 1990;Ghezzi et al, 1991;Ravnborg & Dahl, 1991;Toleikis et al, 1991;Furby et al, 1992;van der Kamp et al, 1996;Mills & Nithi, 1997). The possible influence of these variables on transcranially evoked potentials warrants further investigation in a healthy population.…”
Section: Resultsmentioning
confidence: 99%
“…CMCTðmsÞ ¼ MEP latency À ½1=2 Â ðM latency þ F latency À 1 msÞ MEP latencies are significantly correlated with upper limb length [55,56]. Therefore, MEP latencies were adjusted to upper limb length by dividing the MEP latency (ms) by the upper limb length (m); the adjusted MEP latencies, expressed as ms m À1 , were then used in the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, CMCT has no correlation or only a weak correlation with age ( Ugawa et al, 1989a ; Claus, 1990 ; Eisen and Shtybel, 1990 ; Mano et al, 1992 ; Rossini et al, 1992 ; Mills and Nithi, 1997 ; Matsumoto et al, 2012 ). CMCT for upper limbs has no correlation or only a weak correlation with body height, whereas CMCT for lower limbs is strongly correlated with height ( Rossini et al, 1987b ; Chu, 1989 ; Ugawa et al, 1989a ; Claus, 1990 ; Ghezzi et al, 1991 ; Ravnborg et al, 1991 ; Toleikis et al, 1991 ; Furby et al, 1992 ; Wochnik-Dyjas et al, 1997 ; Matsumoto et al, 2010a ). Most studies show no gender differences in CMCT once data are corrected for height ( Ugawa et al, 1989a ; Claus, 1990 ; Toleikis et al, 1991 ; Furby et al, 1992 ; Mills and Nithi, 1997 ; Tobimatsu et al, 1998 ).…”
Section: Central Motor Conduction Measurementsmentioning
confidence: 99%